Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1007/bf02245056
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 receptor mechanisms in the cognitive performance of young adult and aged monkeys

Abstract: Dopamine (DA) D1 receptor compounds were examined in monkeys for effects on the working memory functions of the prefrontal cortex and on the fine motor abilities of the primary motor cortex. The D1 antagonist, SCH23390, the partial D1 agonist, SKF38393, and the full D1 agonist, dihydrexidine, were characterized in young control monkeys, and in aged monkeys with naturally occurring catecholamine depletion. In addition, SKF38393 was tested in young monkeys experimentally depleted of catecholamines with chronic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
315
14

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 524 publications
(374 citation statements)
references
References 27 publications
35
315
14
Order By: Relevance
“…Other human and animal studies DA modulates responses to positive/negative rewards, salient events and arousal-producing stimuli (Everitt et al, 2000;Liberzon et al, 2003;Horvitz, 2000) CSF HVA levels are related to impulsivity in BPD (Coccaro, 1998;Chotai et al, 1998); to self-injurious and violent behavior (Winchel and Stanley, 1991;Soderstrom et al, 2001) DA receptor activity in the DLPFC modulates working memory and cognition (Arnsten et al, 1994;Goldman-Rakic, 1996;Arnsten and Goldman-Rakic, 1998) DA modulates emotional responses mediated by the amygdala-VTA-PFC circuits (Horvitz, 2000) DA dysfunction is involved in drug addiction (Modell et al, 1993;Volkow and Fowler, 2000) PCP-induced cognitive impairment correlates with DA levels in the DLPFC (Jentsch et al, 1997) Stress alters DA activity in the amydala and PFC (Finlay and Zigmond, 1997;Doherty and Gratton, 1999) DA mediates aggression and attack in rats (Wade et al, 2000;Vukhac et al, 2001) DA modulates cognitive processes at NMDA receptors (Williams and Goldman-Rakic, 1995) DA modulates conditioned fear responses (Guarraci et al, 1999) DA stimulates impulsive behavior in rats (Harrison et al, 1997) D1 agonist dilhydrexidine enhances cognitive performance and stimulates Ach release in the PFC (Steele et al, 1997;Schneider et al, 1994) Microdialysates of the PFC and the NAC suggest DA dysfunction is a risk factor for impulsivity (Van Erp and Miczek, 2000;Dalley et al, 2002) DA dysfunction in the DLPFC is related to cognitive impairment in SCZ, SPD, and normal subjects (Goldberg et al, 2003;Siever et al, 2002) DAFdopamine; CSF HVAFspinal fluid homovanillic acid; DLPFCFdorsolateral prefrontal cortex; PCPFphencylclidine; VTAFventral tegmental area; PFCFprefrontal cortex; AchFacetylcholine; NACFnucleus accumbens; SCZFschizophrenia; SPDFschizotypal personality disorder.…”
Section: The Effects Of Dopamine In Human and Animal Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other human and animal studies DA modulates responses to positive/negative rewards, salient events and arousal-producing stimuli (Everitt et al, 2000;Liberzon et al, 2003;Horvitz, 2000) CSF HVA levels are related to impulsivity in BPD (Coccaro, 1998;Chotai et al, 1998); to self-injurious and violent behavior (Winchel and Stanley, 1991;Soderstrom et al, 2001) DA receptor activity in the DLPFC modulates working memory and cognition (Arnsten et al, 1994;Goldman-Rakic, 1996;Arnsten and Goldman-Rakic, 1998) DA modulates emotional responses mediated by the amygdala-VTA-PFC circuits (Horvitz, 2000) DA dysfunction is involved in drug addiction (Modell et al, 1993;Volkow and Fowler, 2000) PCP-induced cognitive impairment correlates with DA levels in the DLPFC (Jentsch et al, 1997) Stress alters DA activity in the amydala and PFC (Finlay and Zigmond, 1997;Doherty and Gratton, 1999) DA mediates aggression and attack in rats (Wade et al, 2000;Vukhac et al, 2001) DA modulates cognitive processes at NMDA receptors (Williams and Goldman-Rakic, 1995) DA modulates conditioned fear responses (Guarraci et al, 1999) DA stimulates impulsive behavior in rats (Harrison et al, 1997) D1 agonist dilhydrexidine enhances cognitive performance and stimulates Ach release in the PFC (Steele et al, 1997;Schneider et al, 1994) Microdialysates of the PFC and the NAC suggest DA dysfunction is a risk factor for impulsivity (Van Erp and Miczek, 2000;Dalley et al, 2002) DA dysfunction in the DLPFC is related to cognitive impairment in SCZ, SPD, and normal subjects (Goldberg et al, 2003;Siever et al, 2002) DAFdopamine; CSF HVAFspinal fluid homovanillic acid; DLPFCFdorsolateral prefrontal cortex; PCPFphencylclidine; VTAFventral tegmental area; PFCFprefrontal cortex; AchFacetylcholine; NACFnucleus accumbens; SCZFschizophrenia; SPDFschizotypal personality disorder.…”
Section: The Effects Of Dopamine In Human and Animal Studiesmentioning
confidence: 99%
“…The DLPFC is important in the implementation of cognitive control, and the ACC in responding to incongruent stimuli, the monitoring of responses and initiating mid-course corrections in behavior (MacDonald et al, 2000;Shima and Tanji, 1998). D1 receptors predominate in the human cortical mantle (Hurd et al, 2001), and there is strong evidence that DA neurons projecting from the VTA to the DLPFC (Figure 1) serve to modulate working memory and cognition through their effects on D1 receptors (Arnsten et al, 1994;GoldmanRakic, 1996). The effect is bimodal.…”
Section: Da Dysfunction and Impulsive Behaviors In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have demonstrated an important role of the D 1 -like (D 1 ,D 5 ) receptors. Blockade of the D 1 -like receptors in PFC disrupts working memory (Arnsten et al, 1994;Sawaguchi and Goldman-Rakic, 1991). In animals with dopamine depletion, occurring either naturally with aging, or induced by reserpine treatment or chronic stress, the D 1 partial agonist SFK-38393 improves working memory (Arnsten et al, 1994;Mizoguchi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Blockade of the D 1 -like receptors in PFC disrupts working memory (Arnsten et al, 1994;Sawaguchi and Goldman-Rakic, 1991). In animals with dopamine depletion, occurring either naturally with aging, or induced by reserpine treatment or chronic stress, the D 1 partial agonist SFK-38393 improves working memory (Arnsten et al, 1994;Mizoguchi et al, 2000). However, an overflow of dopamine activity, either by excessive dopamine release or overstimulation of postsynaptic D 1 receptor, can impair working memory (Arnsten and Goldman-Rakic, 1998;Cai and Arnsten, 1997;Murphy et al, 1996;Zahrt et al, 1997).…”
Section: Introductionmentioning
confidence: 99%